Fish and Fisheries in Floodplain Swamp in Middle Part of Musi River - Dina Muthmainnah; Abdul Karim Gaffar (Research Centre of Inorganic Materials and Complexs, 2017)
Floodplain area is a very dynamic water system where the influence from terrestrial and river is high. This area is recognized as feeding, nursery and spawning ground of some fishes. Capture fisheries in this area is frequently occurred by using some of specific fishing gears which related to dynamic pattern of aquatic environment, such as water level, current, and physical-chemical aspects of water. The research was conducted in order to evaluate fish caught composition and fishing activity in floodplain swamp in middle part of Musi River by survey method. The result showed that 45 species of fish were caught and nine kinds of fishing gears were used by fishers. Gill nets were used in whole year, while seine were used only in the peak of dry season. Intra-annual variations of swamp water flow can modify the distribution and migratory pattern of fish species, with direct effects on fish catches.